A Study of AgNOR Scores on FNAC of Breast Lumps and Its Correlation with Histopathological Grading - Tasneem, Rumana; M R, Manjunath; Y, Muralidhar Bhat (Annals of Pathology and Laboratory Medicine, 2022)
Background: Breast cancer is one of the leading cancers in women both in developed and developing countries. Nucleolar Organizer Regions (NORs) are loops of DNA related to protein synthesis and ribosomal activity. Argyrophilic Nucleolar Organizer Region (AgNOR) counts act as a reliable cell proliferative marker as they aid in identifying cell proliferation activity and aggressiveness of a lesion, and thereby helps in differentiating benign and malignant breast lesions. Aim: To evaluate the role of AgNOR count in differentiating benign and malignant breast lumps. Methods: All breast lump specimens collected for Fine Needle Aspiration Cytology (FNAC) and histopathology, for a period of one year, were included in the study. A total of 69 specimens were included. All FNAC and histopathology slides were stained with AgNOR stain, and the score was recorded. Result: A total of 69 cases were studied, both non-neoplastic and neoplastic breast lesions. All FNAC cases correlated histologically. Out of the 69 cases, 38 were malignant. The mean AgNOR counts in non-neoplastic, benign and malignant breast lesions were found to be 2.19, 2.88 and 5.94 respectively (p<0.05). Other parameters such as proliferative AgNOR index, AgNOR size variation, AgNOR distribution within the nucleus and the Subjective AgNOR Pattern Assessment (SAPA) scores also showed statistically significant difference between benign and malignant lesions. Conclusion: AgNOR scores showed good correlation in differentiating benign and malignant breast lesions, they can be used as a reliable tool to aid in the diagnosis.